Symmetric functions of the k-Fibonacci and k-Lucas numbers - Acikgoz, Mehmet; Boussayoud, Ali; Kerada, Mohamed; Araci, Serkan; Aracı, Serkan (World Scientific Publishing Co. Pte Ltd, 2020)
In this paper, we introduce a new operator in order to derive some new symmetric properties of k-Fibonacci and k-Lucas numbers and Fibonacci polynomials. By making use of the new operator defined in this paper, we give some new generating functions for k-Fibonacci and Pell numbers and Fibonacci polynomials. © 2020 World Scientific Publishing Company.
Keywords: Fibonacci polynomials; generating functions; k-Fibonacci numbers; k-Lucas numbers